Analisa Potensi Pengembangan Energi Alternative Berbasis Limbah Kelapa Di Kabupaten Indragiri Hilir - Khairul Ihwan; Roberta Zulfhi Surya (JUTI UNISI, 2019)
Indragiri Hilir Regency has the largest coconut plantation in Indonesia with coconut production reaching 390,924.28 tons per year and land area of ​​295,380.24 hectares (BPS Inhil Regency, 2012). According to Palunkun in Prananta (2004) the composition of coconuts consists of coir 35%, coconut shell 12%, fruit flesh 28% coconut water 25%. So the number of coir and coconut shell that has been burned is 47% of the production of coconut grains. So that coir and shell waste is 643,070,441 tons of waste. Based on research that has been done in the area of ​​extranmigration in Pelangiran sub-district and Belengkong bay sub-district, the potential of coconut waste in the form of coconut fiber is 7,406,000 kg. if the coconut plantations are harvested at the same time. The duration of the harvest for 2.5 to 3 months each time. So that the potential of coconut waste (coconut husk) is 82.288.89 kg / day multiply the calorie value of coconut fiber at 4.004.8 k.cal is 329,546,982.40 K. Kal / kg. if converted into electrical energy with a conversion factor of every tonne of calories is 1.1628x 10-3 MWh (Energy Outlook Statistics, University of Indonesia, 2000) then the potential electrical energy from waste to be produced is 329,546.98 Ton K.Kal X 1 , 1628 x 10 -3 MWh. = 0.383263 Kwh.